Thin-layer drying behaviour of mint leaves - Doymaz, I (ELSEVIER SCI LTD, 2006)
The thin-layer drying behaviour of mint leaves for a temperature range of 35-60 degrees C was determined in a cabinet dryer. The increase in air temperature significantly reduced the drying time of the mint leaves. Drying data of this material were analysed to obtain diffusivity values from the falling rate-drying period. In this period, moisture transfer from mint leaves was described by applying the Fick's diffusion model. Effective diffusivity varied from 3.067 x 10(-9) to 1.941 x 10(-8) m(2)/s and increased with the air temperature. An Arrhenius relation with an activation energy value of 62.96 kJ/mol expressed effect of temperature on the diffusivity. Four thin-layer drying models available in the literature were fitted to the experimental data. Among all the drying models, the logarithmic model was found to satisfactorily describe the kinetics of air-drying of mint leaves. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: modelling; mint leaves; drying; diffusivity; activation energy; KINETICS; DEHYDRATION; PARAMETERS; DRYER; GREEN; Engineering; Food Science & Technology